THE ROLE OF RISK MANAGEMENT IN ACHIEVING ACCOUNTABLE LOCAL GOVERNMENT ASSET GOVERNANCE - Andi Mahdiana Mardatillah; Nur Fadilla Guntur; Muhammad Iqbal (Universitas Cahaya Prima, 2026)
Effective regional asset management is essential for ensuring public accountability, administrative efficiency, legal certainty, and optimal public service delivery. However, local governments continue to face various asset-related risks, including incomplete asset records, uncertified land, unauthorized utilization, legal disputes, inadequate data quality, and limited institutional capacity. This study aims to examine the role of risk management in strengthening accountable local government asset governance. The study employed a qualitative library research approach using a descriptive-thematic analysis of relevant academic literature, government regulations, policy documents, and institutional reports. The findings indicate that risk management has an important strategic role in regional asset governance through risk identification, assessment, mitigation, monitoring, and reporting across the asset life cycle. Nevertheless, its implementation remains constrained by weaknesses in asset data quality, limited digital infrastructure, insufficient human-resource capacity, inconsistent risk awareness, and legal and physical vulnerabilities of regional assets. Strengthening risk management requires integrated asset information systems, systematic asset verification and certification, stronger internal controls, continuous capacity development, leadership commitment, and the establishment of a risk-aware organizational culture. The study concludes that integrating risk management into regional asset governance can reduce the potential for asset loss and disputes, improve asset utilization and reporting reliability, and strengthen transparency and accountability. A risk-based approach therefore provides an important foundation for creating sustainable and accountable local government asset governance.